Oral Primary Syphilis - A Rare Case Report - M C Shashikanth; Sheeba Mohindra (Wolters Kluwer Medknow Publications, 2004)
Syphilis is a sexually transmitted disease caused by spirochete, Treponema palladium. The incidence of syphilis has greatly increased in the past few years, though oral disease as a consequence of primary syphilis is rare. Extragenital chancres occur in about 5-10% of cases with primary syphilis and may occur as a consequence of orogenital contact. We report a case of 40 year old man, with primary syphilis, who presented with ulceration in the palate and non tender lymphadenopathy. The oral aspects of primary syphilis and the need for dentists to be aware of changing epidemiologic trends are highlighted.